On Approximation of Function Classes in Lorentz Spaces with Anisotropic Norm (Analysis in Theory and Applications, 2013)
In this paper, Lorentz space of functions of several variables and Besov's class are considered. We establish an exact approximation order of Besov's class by partial sums of Fourier's series for multiple trigonometric system.